Timely Initiation of Complementary Feeding and Associated Factors among Mothers of Children Aged 6–24 Months in Dessie Referral Hospital, Northeast Ethiopia, 2019 - Atsedemariam Andualem; Afework Edmealem; Belachew Tegegne; Lehulu Tilahun; Yitayish Damtie (Journal of Nutrition and Metabolism, 2020)
Background. Timely, appropriate, safe, adequate, and frequent feeding is essential during the transition period for optimal growth and development as well as vulnerability of the child. The age of initiation of complementary feeding needs to be strongly addressed. Thus, the aim of this study was to determine timely initiation of complementary feeding and associated factors among mothers of children aged 6–24 months in Dessie Referral Hospital. Methods. Institutional-based cross-sectional study was conducted among 280 mothers of children aged 6–24 months. A systematic random sampling technique was employed for selection of study participants by considering the 1st comer as a starting point and then at every 5th interval till the sample size was saturated at exit time. Data were collected using pretested and validated structured interviewer-administered questionnaire. Data were entered to Epi data version 3.1 and exported to SPSS version 20.0 software for analysis. Descriptive statistics and binary logistic regression model were used. Results. Overall response rate was 98.2%. Among 275 mothers with children aged 6–24 months, 36 (13.1%), 179 (65.1%), and 60 (21.8%) mothers started giving complementary feeding for their children early (before six months), timely (at six months), and late (after six months), respectively. Mothers’ educational status of grade 9–12 and college and above [AOR = 3.03; 95% CI (1.13–8.14), and AOR = 3.74; 95% CI (1.19–11.70), respectively], getting counsel [AOR = 2.83; 95% CI (1.54–5.21)], and poor knowledge [AOR = 0.37; 95% CI (0.19–0.72)] were found to be independent predictors. Conclusions. Prevalence of timely initiation of complementary feeding was high as compared to the national prevalence. Mothers’ educational status, getting counsel about complementary feeding, and knowledge were factors associated with timely initiation of complementary feeding. Therefore, awareness creation, counseling, and health education should be done on society by concerned bodies to improve timely introduction of complementary feeding level more than this result.